Deficiência de tiamina e isolamento social afetam aspectos do comportamento motor e níveis centrais de GABA e glutamato - Ana Raquel Pereira Caixeta (2011)
The main phenomenon approached in this study is the motor behavior, evaluated after two different types of environmental stimuli, the consumption of diet deficient in B1 vitamin and/or social isolation. The B1 vitamin, thiamine, is an essential nutrient for the nervous tissue. In previous studies, our research group has shown that the maternal thiamine deficiency can lead to decreased brain weight, induces modifications in the motor behavior and neurochemical changes in the Central Nervous System (CNS) of the offspring. Social isolation, on the other hand, is considered an environmental impoverishment, and has been seen as an important paradigm in studies of mild chronic stress, and in understanding the genesis of depression, emotional disturbances and cognitive deficit. As far as you know, there are no literature data about the effects of social isolation on behavioral motor. Considering the importance of thiamine and social life for brain neurochemistry homeostasis, the objectives of the present study were to investigate the effects of severe thiamine deficiency and/or social isolation on the motor activity and neurochemical parameters of rats in adulthood. Forty-two Wistar rats, 3 months old, were divided in four experimental groups: isolated deficient (n=13), grouped deficient (n=8), isolated standard (n=13) and grouped standard (n=8). All animals were submitted to behavioral tests (Beam Balance, Rotarod e Paw print) for analysis of the motor behavior aspects (balance, path length and width path). After behavioral tests, the animals were killed by decapitation and the cerebellum, striatum, thalamus and prefrontal cortex were removed for analysis of the GABA and glutamate concentrations using the High Performance Liquid Chromatography (HPLC) method. It was observed that the thiamine deficiency reduced significantly the animals permanency on the Beam Balance [p = 0,000] and the Rotarod 5rpm [p = 0,0012] and 25 rpm [p = 0,000]. Similarly, the social isolation also decreased the animals permanence on the Beam Balance [p = 0,002] and the Rotarod 5rpm [p = 0,002] and 25 rpm [p = 0,000]. Thiamine deficiency significantly increased the animals path width [F(1,34) = 47,861; p = 0,000]. Thiamine deficiency also significantly decreased cerebellar glutamate [F(1,34) = 5,032; Abstract p = 0,032] and GABA [F(1,34) = 9,471 ; p = 0,004] concentrations. Besides decreasing significantly the glutamate [F(1,34) = 186,044; p = 0,000] and GABA [F(1,34) = 26,498 ; p = 0,000] concentrations , the isolation also decreases the glutamate concentration in the thalamus [F(1,34) = 129,557; p =0,000], in the prefrontal cortex [F(1,34) = 100,511; p =0,000] and increased the GABA concentration in the striatum [F(1,34) = 11,610; p = 0,002]. A significant correlation was not observed between the motor parameters evaluated and neurochemical parameters. In conclusion, thiamine and relationship among subjects are important to the central GABA/glutamate homeostatic balance and motor activity. In addition, the results suggest that: (i) the thiamine effect on behavioral motor aspects depends on the environmental conditions animals kept in group or isolated, and (ii) cortical levels of GABA seem to be involved in tuning motor activity.